Income, work, and health satisfaction differ primarily by household income, age, and parental status - Laura Buchinger; Theresa Margareta Entringer; Daniel Graeber (DIW Weekly Report, 2024)
Subjective well-being is essential for both quality of life and a healthy society. Studies have shown that satisfied people have better relationships, are more productive, and have a longer life expectancy. General life satisfaction is being discussed as an alternative measure of prosperity beyond GDP. Thus, findings on this topic are relevant for both the scientific community as well as policymakers. This Weekly Report investigates the income, work, and health satisfaction of the German population from 2004 to 2021. Using data from the Socio-Economic Panel, we investigate if there are differences in satisfaction between genders, regions (east/west), age groups, parental status, and income groups. The analysis shows that general life satisfaction as well as income, work, and health satisfaction have either increased or remained constant since 2004. However, differences between groups, some quite significant, still remain, especially in terms of health satisfaction. Comparatively, low-income earners and parents are dissatisfied. To counter this, policy measures to unburden parents and improve the childcare system are needed.
Keywords: D60; D63; 330; Well-being; satisfaction; domains; inequality